CORRELATION AND PATH ANALYSIS OF TOMATO CROP (Solanum lycopersicum L.) UNDER PROTECTED CONDITIONS - LEKSHMI S. L *; V. A. CELINE (The Journal of Research ANGRAU, 2020)
Tomato genotypes ( 40 no.) were studied for eight quantitative characters from October 2014 to April 2015 to assess the nature and magnitude of genetic variability under protected conditions. A wide range of variation was noticed among the characters studied.The genotypic correlation coefficients were similar in nature and higher in magnitude than the corresponding phenotypic correlation coefficients. Yield recorded positive correlation with fruits per plant (0.6224), truss per plant (0.7809), fruits per truss (0.6720) and fruit weight (0.6360). Path analysis revealed considerable positive indirect effects on yield per plant as exerted by fruits per plant, truss per plant, fruit length, fruit weight and fruit girth. Highest positive direct effect was recorded for fruit weight (0.3956) followed by truss per plant (0.3558) and fruits per plant (0.3381). This indicates the importance of these characters in yield improvement programme in tomato under protected conditions.